Analisis Kemampuan Pemecahan Masalah Siswa pada Materi Bangun Ruang Sisi Datar - Nuraini Nadhifa; Maimunah Maimunah; Yenita Roza (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2019)
The low mathematical problem solving ability of students is seen from the results of the national exam on mathematics subjects, namely 43.34%. This study aims to describe the ability to solve mathematical problems based on policy theory which consists of 4 stages (1) understanding, (2) planning, (3) solving, and (4) checking. The subjects studied were 30 students of VIII class. The method used is descriptive qualitative. Data collection techniques with test and interview methods Instrument-used 3 questions which are mathematical problems related to the surface area and volume of building flat side space. The results of this study indicate that students who have the ability (1) are very good, often forget to write what is known and what is asked, (2) at a good level, students have difficulty understanding and making a mathematical model of the problem editor, (3 ) at a low level, students make mistakes in calculating, (4) At a very poor level, students have difficulty understanding and making mathematical models and their solutions. It is expected to the teacher to give emphasis on understanding the concept of flat and wake up flat side space when the learning process takes place and associate it in everyday life, because most students have difficulty in understanding and making mathematical models of the editorial questions given.